42. CLINICAL MANIFESTATIONS AND RELATED FACTORS OF VITILIGO AT THE NATIONAL HOSPITAL OF DERMATOLOGY AND VENEREOLOGY IN VIETNAM FROM 2016 TO 2017 (Vietnam Journal of Community Medicine, 2024)
Objectives: Examine clinical manifestations and associated factors of vitiligo patients at the National Hospital of Dermatology and Venereology (NHDV) from 2016 to 2017. Materials and methods: A cross-sectional descriptive study of 80 patients diagnosed with vitiligo at the NHDV from 10/2016 to 9/2017. Results: The average age of disease onset is 26.89 ± 18.38, of which the age group of 15 to 30 years old accounted for the highest proportion (40%). The incidence rate of women was higher than that of men (56.2% vs 43.8%). The rate of comorbidities explored via asking patient’s history was 17.5%, including gastric and duodenal ulcers, atopic dermatitis and allergic diseases, and history of thyroid disease was not reported. Patients with vitiligo having skin type IV accounted for 93.7% and skin type III accounted for 6.3%. The most common location of lesions was the face and neck, accounting for 46.3%, followed by the trunk (24.3%) and the extremities (1.5%). The main clinical type was non-segmental generalised vitiligo (46.3%) while the segmental type accounted for only 2.5%. Seventy one of 80 patients were in active disease stage (with VIDA score of +1,+2,+3,+4) accounting for 88.7%, in which VIDA score of +4 accounted for the highest proportion (38.7%). Conclusion: In our study, vitiligo was common in young people, and the disease can occur in both men and women. The disease was mainly seen in patients with skin type IV and non-segmental generalised vitiligo was the most common form. A patient can have multiple lesion locations, and the mostly involved locations were face and neck.
Keywords: Vitiligo, VIDA.